Riverbank settlement and humanitarian architecture, the case of Mangunwijaya’s dwellings and 25 years after, Code river, Yogyakarta, Indonesia - Idham, Noor Cholis (Journal of Architecture and Urbanism, 2018)
Code riverbank has drawn worldwide attention since 90’s when Architect Mangunwijaya involved in the dispute of urban riverside settlement in Yogyakarta. Struggling for the slum between the municipality and the dwellers gradually dwindled, and one of most significant causes was his humanitarian dwelling self-help scheme on Kampung Code. The project, which was later recognized by Aga Khan Award for Architecture in 1992, was not only purposed for reducing the tension but also promoting appropriate social order by considering the natural environment vulnerability. One of the poorest and most crook riverbank zones of the city had transformed to be a better environment with positive atmosphere afterward. Unfortunately, the project was hardly followed by other dwelling construction either in the site or other parts of the bank. This paper studies how the architecture could cure the social problems as well as resolve the environmental challenges and its sustainability. The social approaches done by Mangunwijaya and how he captured the high-risk of riverbank nature to the dwelling concepts were accessed. The results indicate that in spite of the riverside’s slum controversies, the architecture should be considered as a remedy both for social and natural problems.